Online Feedback Analysis of Current Teaching Methodology in Anatomy and Physiology Medical Research Practice Among Medical Under Graduates at Sharda University - Rastogi, Shalini; Rohatgi, Rachna; Gupta, Nirupma; Nandkeoliar, Manoj Kumar; Rastogi, Sonal; Rastogi, Vichal (Journal of Neonatal Surgery, 2025)
Introduction: Complex links between anatomy, physiology, and clinical sciences are crucial for both disease diagnosis and managementas it causes structural alterations or anatomical deformities. Future medical professionals must therefore have sufficient anatomical and physiology knowledge that leads to an impactful medical learning depends upon a strong medical teaching system. Therefore, feedback analysis assessment was done of current medical teaching methodology and trends in Anatomy and Physiology medical research practice among medical undergraduates at Sharda University. Method: A self-structured online questionnaire survey was conducted among 250 medical undergraduates at Sharda University. Questionnaire dealt with teaching methodology in anatomy and physiology medical research practice containingone appropriate answer. Collected data was analysed using SPSS version 23 and p-Value<0.05 was considered significant. Result: About (60.3%) of subjects considered 45 minutes as the ideal duration for theory class and asking query from friend at first bench was relevant among (56.2%) study subjects. About (13.8%) study subjects inclined for research at genetic level to understand the etio-pathogenesis of a disease and (23.7%) thought that research is unpopular in country due to poor funding aid by government towards health care. Conclusion: It was found that for an MBBS undergraduates to receive better and more thorough training and become a qualified physician, modified teaching strategies should be developed.